NCOG-20. LONGITUDINAL ASSESSMENT OF SUBJECTIVE COGNITIVE FUNCTION IN ADULTS WITH LOW GRADE GLIOMA TREATED WITH PROTON RADIATION THERAPY. (12th November 2021) - Zarrella, Giuliana; Parsons, Michael; Sherman, Janet; Dietrich, Jorg; Shih, Helen
Abstract: INTRODUCTION: Our group previously demonstrated stability in neurocognitive function (NCF) over a 5-year period after proton radiation therapy (PRT) in low grade glioma (LGG) patients. Subjective cognitive function (SCF) had not been previously explored, nor had individual analyses of cognition, which can detect variability in trajectory. We used the newly derived Functional Assessment of Cancer Therapy-Brain Cognitive-Index (FACT-Br-CI) to examine SCF in LGG patients after PRT and compare longitudinal changes in SCF and NCF. METHODS: 20 LGG patients ( M age =37.5) treated with PRT completed NCF tests and self-report measures annually for 5 years or until tumor progression. Group change in SCF was examined with paired t-test (baseline vs final FACT-Br-CI). Individual change scores were calculated for FACT-Br-CI and NCF tests (clinical trials battery composite; CTBC). Individual deterioration in NCF was defined by reliable change index (RCI) on CTBC, and in SCF was defined as decline of >/=1 SD in FACT-Br-CI. Relationships between change in SCF and NCF were explored with correlations. RESULTS: At the group level, no change was observed in FACT-Br-CI between baseline and last follow-up ( t (19)=-.91; p =ns). Individual SCF analyses at last follow-up found the number of patients reporting decline=3 (15%), improvement=5 (25%), and no change=12 (60%). Individual changes were observed in SCF in 20% of patients at 3 months, 5.9% at 6 months, 12.5% at 12 months, 13.3% at 24 months, and 11.1% at 36 months. Median time to any deterioration in SCF was 36 months and for NCF was not reached. Correlation between CTBC and FACT-Br-CI change scores did not reach statistical significance ( r =.41; p =ns). CONCLUSION: Consistent with previous research, group analyses of LGG patients did not show cognitive decline after PRT. However individual analyses of SCF showed variability within the group: some patients experienced cognitive decline during follow up. Consideration of individual differences may yield additional information.